Study on Continuous Adsorption Process for Monoethanolamine (MEA) Wastewater Treatment Using Granular Activated Carbon and Sugarcane Bagasse - Muhammad Noor Azreen, Mohd Khairu (2013)
Monoethanolamine (MEA) is one of the most widely used alkanolamines for removing sour gases such as H2S and CO2 from natural gas for refining processes. MEA has gained attention for the abatement of greenhouse gases and the disposal of the MEA wastewater causing a problem as MEA cannot be treated easily due to its toxic effect and slow biodegradability. Foaming phenomena is formed in the absorber when heavy hydrocarbon component carried to the absorber with the feed gas that will leads to several problems such as increased amine losses, reduced gas adsorption efficiency and MEA feed back into the stripper as properties deterioration. This study was conducted to determine potential of continuous technique for treating MEA wastewater and to evaluate the potential of recycling on the treated MEA wastewater. Adsorption method was used for the treatment adsorbent of granular activated carbon with sugarcane bagasse as the comparison of these two adsorbents was investigated. Three parameters have being analysed which is the removal of oil content, amine concentration and COD level. The results showed that activated carbon was the best adsorbent for MEA wastewater treatment system. At the optimum condition, amine concentration is maintained and the residue oil reached its highest removal percentage of 91.72% and COD level reduction of 61.04% approximately via activated carbon adsorption treatment.